Development of Big Data Analytics Technology on Sea Freight Operational Performance Using the Agile Model - Wahyudin, Agus; Bani, Fajar Ciputra Daeng; Ibrahim, Arief Budi (PT. Riset Press International, 2024)
The development of industry 4.0 is still difficult for a country to produce all goods according to the required needs. Big data analytics technology has the potential to revolutionize how logistics companies, including freight forwarders, can facilitate real-time monitoring in the supply chain by increasing flexibility. Management information systems produce a number of data from different sources and in different formats according to business needs. The development of big data analytics uses a dynamic system development method or model (DSDM), which is a dynamic system development model that uses a rapid application development (RAD) approach. Software development with an emphasis on collaboration, customer engagement, and continuous delivery of working software. This model is very suitable for the development of big data analytics technology that can provide solutions that often involve complex and rapidly changing requirements with large amounts of data and the business need to provide feedback from stakeholders in real-time. It is hoped that the final results of this research will provide insight into sea freight operations that are more informative and efficient for the logistics industry in Indonesia.